Pengaruh Profitabilitas, Solvabilitas, dan Likuiditas Terhadap Opini Audit Going Concern - Siti Utari; Susy Hambani; Maria Magdalena Melani (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
Financial reports include details on the company's financial situation over a specific time period, however because of the information that is provided so sparingly, the financial report actually still has flaws. Therefore, it is essential to have an auditor in place who is in charge of checking financial data pertaining to business continuity. The purpose of this study is to ascertain how profitability, solvency, and liquidity affect going concern audit opinions in the Indonesia Stock Exchange (BEI) 2018–2022 Textile and Garment Sub-Sector. This study's data analysis approach makes use of quantitative analysis techniques. The findings of the study demonstrate that, for the years 2018–2022, the going concern audit opinion is positively and significantly impacted by profitability, solvency, and liquidity all at the same time. On the other hand, the going concern audit opinion is negatively and negligibly impacted by partially profitable operations, negligibly impacted by solvency, and significantly impacted negatively by liquidity.